Implementation of Dakon Game in Elementary School Mathematics Learning - Eko Sujaryanto (Javanologi: International Journal of Javanese Studies, 2025)
The dakon game, as one of the traditional games that has been widely known in Indonesia, has great potential to be integrated into mathematics learning in elementary schools, especially in the material of integer arithmetic operations. This article aims to analyze the benefits and applications of dakon as an interactive learning media that supports the understanding of the concepts of addition, subtraction, multiplication, and division of integers. With a game-based learning approach, dakon not only functions as a learning aid, but is also able to increase students' motivation in learning mathematics. This game makes it easier for teachers to explain abstract concepts in a more concrete and interesting way. The results of the study show that the integration of the dakon game in mathematics learning can improve students' understanding of integer arithmetic operations, train critical thinking skills, and encourage collaboration among students. In addition, the use of dakon in learning is in line with the principle of independent learning which emphasizes a fun and meaningful learning experience. By making dakon part of the learning strategy, teachers can create a more dynamic and interactive learning atmosphere, so that students can more easily understand the material and be actively involved in the learning process. The novelty of this research lies in its systematic exploration of how local cultural heritage—in the form of the dakon game—can be transformed into a structured pedagogical model for teaching arithmetic, which has not been widely implemented or documented in formal education contexts. This article recommends the dakon game as a strategic innovation in mathematics learning, especially to improve the quality of learning in elementary schools.